2019
DOI: 10.1080/2162402x.2019.1655362
|View full text |Cite
|
Sign up to set email alerts
|

PDL1 expression is associated with longer postoperative, survival in adrenocortical carcinoma

Abstract: Adrenocortical carcinomas (ACCs) are heterogeneous cancers associated with a very poor prognosis. The improvement of prognostic tools and systemic therapy are urgently needed. Targeting the immune system using checkpoint inhibitors such as PD1/PDL1 inhibitors is an attractive novel therapeutic strategy for poor-prognosis tumors. Multiple clinical trials are ongoing, including in advanced ACC. However, PDL1 expression has been studied in ACC in only one heterogeneous series of 28 clinical samples. Here, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…In addition, large tumour size and cortisol-secreting tumour were additional factors for ACC-specific death [ 49 ]. Moreover, there are many predictive features proposed for the prognosis of patients with ACC such as mitotic grading [ 52 ], Ki-67 index [ 75 ], mi-RNAs expression [ 76 ], expression of PDL-1 [ 77 ], SF-1 [ 78 ] and sterol-O-acyl transferase 1 (SOAT1) [ 79 ]. Preliminary data also shows that for localised ACC, molecular makers (expression, methylation, and chromosome alterations) could predict cancer recurrence [ 9 ].…”
Section: Conventional Adrenocortical Carcinomamentioning
confidence: 99%
“…In addition, large tumour size and cortisol-secreting tumour were additional factors for ACC-specific death [ 49 ]. Moreover, there are many predictive features proposed for the prognosis of patients with ACC such as mitotic grading [ 52 ], Ki-67 index [ 75 ], mi-RNAs expression [ 76 ], expression of PDL-1 [ 77 ], SF-1 [ 78 ] and sterol-O-acyl transferase 1 (SOAT1) [ 79 ]. Preliminary data also shows that for localised ACC, molecular makers (expression, methylation, and chromosome alterations) could predict cancer recurrence [ 9 ].…”
Section: Conventional Adrenocortical Carcinomamentioning
confidence: 99%
“…Many cancer-promoting factors play a role in the EMT pathway (43). For instance, the expression of PDL1 can affect the prognosis of adrenocortical carcinoma (44). Regardless of stromal or immune cells, the C2 and C3 subtypes displayed more characteristics of TME.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric ACC, MHC class II expression by tumor-infiltrating hematopoietic cells and the number of CD8 + T-lymphocytes are important prognostic indicators [13,20]. Even if in general only a small percentage of ACC tumor cells express PDL1, as detected by IHC [17,18], higher levels of PDL1 mRNA expression are significantly correlated with an inflammatory gene expression signature and longer DFS of adult patients with ACC [21]. Furthermore, an unpublished study from the Würzburg group has shown that the number of tumor-infiltrating CD4 + and CD8 + T-lymphocytes are stage-independent prognostic indicators in patients with ACC and that glucocorticoid excess is associated with T-cell depletion and unfavorable prognosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…The three other data sets (110 ACC and 18 normal adrenal samples) were not annotated for both expression and prognostic/survival data. Data analysis required pre-analytic processing, as previously described [21]. To explore more-in-depth the biological pathways associated with FATE1 mRNA expression in ACC, we applied a supervised analysis to the whole TCGA data set as a learning set (n = 79) and compared the expression profiles of all genes between tumors with low versus high FATE1 mRNA expression using a moderated t-test with the following significance thresholds: p < 0.05, q < 0.25 and fold change (FC) higher than |2×|.…”
Section: Gene Expression Analysis In Adult Acc Cohortsmentioning
confidence: 99%